Simplified Hydraulic Design Procedure for Drop Spillway - Kumar, Satyendra; Sirothia, N N (Journal of Agricultural Engineering, 2002)
A study was conducted to give a simple and quick procedure for determining the hydraulic design dimensions of drop spillways. The design discharges and drops were taken from the structures made by the Department of Soil conservation, Govt. of Uttar Pradesh. Ten rational kinetic energy groups of flowing water ranging from 50 kg-m/sec to 10,000 kg-m/sec were obtained using the field data of drops and discharges. Determination of dimensions of different component of drop spillway have a complex and lengthy SAF design procedure (Suggested by Blaisdell and Donnelly) and due to this reason the SAF procedure is rarely adopted in India. Different regression models were tested on design values obtained with SAF procedure and found a very strong power function relationship between product of kinetic energy and critical depth of water flowing (KE X d) and design dimensions of the structure. Co-efficient of determination (RÂ²) were ranging from 0.9974-0.9999 for developed mathemitical equations.